FAKTOR-FAKTOR YANG MEMPENGARUHI PROSES PENYUSUNAN APBD DAN DAMPAKNYA TERHADAP KUALITAS APBD (Studi Di Pemerintah Provinsi Riau Tahun Anggaran 2015) - Lestari, Dince Suci; Rakhmawati, Andewi (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to identify and analyze the effect of executive and legislativerelations, public transparency, public participation, and educational background onbudget process and budget quality of budget process as an intervening variable.Thepopulation in this study was the Riau provincial government as the executive, RiauProvincial Assembly Members as the legislatives and the Non GovernmentalOrganization (NGO) as the representative of the community. The number of samples inthis study were 145 samples with purposive sampling method. There were 125respondents who had returned the questionnaire. The analysis tool used was pathanalysis.Results of the analysis showed that executive and legislative, publictransparency, and educational background direct affects the budget quality.Furthermore, there were no significant effect of community participation. While thisstudy showed that the budget process is able to mediate effect of executive andlegislative relations, public transparency, and educational background on the budgetquality, but the budget process is unable to mediate public participation on the budgetquality.